2012
DOI: 10.1080/15287394.2012.697834
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Diuron on Male Rat Reproductive Organs: A Developmental and Postnatal Study

Abstract: This study was performed to determine whether developmental exposure (perinatal and juvenile) to the herbicide diuron exerted adverse effects on adult rat male reproductive system. Pregnant Sprague-Dawley rats received basal diet or diet containing diuron at 500 or 750 ppm from gestational day 12 (GD 12) until the end of lactation period (postnatal day 21, PND 21). After weaning male offspring received basal diet or diet containing diuron until PND 42 (peripubertal age). At PND 90, adult male rats from each ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…The study is similar to OECD TG 407, Repeated dose 28-day study. The study by Fernandes et al in 2012 is more similar to TG 416 since both pregnant rats and male offspring were exposed to diuron. Both studies by Fernandes focused on endpoints of male reproductive toxicity and the only indication of adverse effects were the reduction of number of pups in the older study (2007) and reduced body weight of offspring in the later study (2012).…”
Section: Comparison With Oecd Cf Methodsmentioning
confidence: 61%
See 1 more Smart Citation
“…The study is similar to OECD TG 407, Repeated dose 28-day study. The study by Fernandes et al in 2012 is more similar to TG 416 since both pregnant rats and male offspring were exposed to diuron. Both studies by Fernandes focused on endpoints of male reproductive toxicity and the only indication of adverse effects were the reduction of number of pups in the older study (2007) and reduced body weight of offspring in the later study (2012).…”
Section: Comparison With Oecd Cf Methodsmentioning
confidence: 61%
“… TG 407 and TG 408 is adequate for evaluation of diuron If the effects of diuron on both rats (Fernandes et al 2007, Fernandes et al 2012, Grassi et al 2011) and lizard (Cardone et al 2008) are considered, it seems that diuron may have both estrogenic-and androgenic effects on animals.…”
Section: Comparison With Oecd Cf Methodsmentioning
confidence: 99%
“…The findings of present study are in agreement with previous studies. [15][16][17][18] On the contrary, other studies reported none of such adverse effects. Those previous studies reported no adverse effects of rhINFα-2b on the spermatogenesis.…”
Section: Discussionmentioning
confidence: 90%
“…Exposure of adult male rats to diuron (Fernandes et al, 2007), or perinatal and juvenile diuron-exposure of male rats (Fernandes et al, 2012) did not alter plasma testosterone levels, daily sperm production or sperm morphology and motility. In the sea urchin, exposure to diuron caused malformations of the embryos and inhibited the fertilization rate (Manzo et al, 2006), whereas in lizards, testosterone levels were significantly decreased (Cardone et al, 2008).…”
Section: Contents Lists Available At Sciencedirectmentioning
confidence: 80%